Hulhopperne – Overordning og sårbarheder i begærssubjektiverede maskuliniteter - Cawood, Sarah Højgaard (Kvinder, Køn & Forskning, 2008)
The article analyses sexulaized media's message to boys to take up heterosexual desire as an active desiring position. This desire is constituted by the media as a possibility to dominate through its impersonal and sometimes subject-destructive character. The boys take up these aspects of the desire position in different ways, but common to them is the way they usually work though humour as a subjectivitytrack. The article suggests that the masculine desiring position entails certain tabooed vulnerability potentials for the boys. The way the masculine desire is constituted with strong dominating/subjectifing aspects opens up a variety of vulnerable posibilties for boys. Among which the article focuses on the policing to take on pornographic desire, the management of explicit sexuality, the sexual drive as compulsive and the position as mastering the sexual experience, as well as selfloathing among those boys who are subjectified as open to feminine subjects' experiences. Furthermore, the construction of pornographic desire underlying much of the sexualized media, entices boys to split up girls into categories of de-humanised screaming pornographic women and the emotionally relating girls, the boys know from their everyday lives.